Double Endoprosthesis in the Management of Refractory Metastatic Primary Bone Tumors in Children and Young Adults. (23rd July 2021) - Raciborska, Anna; Malesza, Iwona; Bilska, Katarzyna; Koziński, Tomasz; Pachuta, Bartosz
Abstract : Background . Although not all children can be cured yet, much more emphasis is placed on the quality of life during and after cancer treatment. In the case of recurrence, mutilating treatment is still the prevalent option. In our study, we explored the role of limb salvage surgery for young patients with metastatic malignant bone tumors after endoprosthesis reconstruction during the first line of treatment and evaluated the impact of the local control modality in disease control and functional outcomes. Materials and Methods . Eleven patients with bone tumor treated between 2007 and 2018 were included in this study. Both during primary treatment and during recurrence, limb salvage surgery was performed using a modular or expandable custom-made replacement system. Peri- and postoperative care for both surgeries were similar. All patients were given chemotherapy before and after both surgeries, according to the oncological guidelines. Results . Seven patients (63.6%) are alive with a median follow-up of 6.5 years from diagnosis. None had local recurrence. Five-year estimates of event-free survival and overall survival were 36.27% and 79.55%, respectively. Median time between the first and second surgery was 2.7 years. Three patients presented with postoperative complications following both surgeries and required resurgical intervention. Three months following the second surgery, the Musculoskeletal Tumor Society Scale (MSTS) scores were 15–27 points (21 points on average—60%). Conclusions . Limb salvage surgery is feasible and offers good chance of cure with a reasonable rate of complications and good function in patients with recurrent bone sarcoma after endoprosthesis reconstruction during the first line of treatment.